1979
DOI: 10.1017/s0021859600039009
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of winter oil-seed rape: occurrence, effects and control

Abstract: SUMMARYThe results of observations begun in 1973 and of disease surveys carried out on winter oil-seed rape crops on ten farms in Hertfordshire and Bedfordshire between 1975 and 1978 are reported. The major diseases encountered in the surveys, namely downy mildew (Peronospora parasitica (FT.) Tull.), canker (Leptosphaeria maculans (Desm.) Ces. & de Not.), light leafspot or scorch (Pyrenopeziza brassicae Sutton & Rawlinson) and grey mould (Botrytis cinerea Fr.) are discussed in relation to diseases of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Sudarmadi and Wallace (1984) reported that benomyl infused into seed via acetone reduced cankering in the crop. Similarly, Verma and McKenzie (1982), Verma et al (1983b), Rawlinson and Muthyalu (1979), and Anderson (1983) reported that some seed dressing fungicides reduced stem canker in older rapeseed plants.…”
Section: Controlmentioning
confidence: 91%
See 1 more Smart Citation
“…Sudarmadi and Wallace (1984) reported that benomyl infused into seed via acetone reduced cankering in the crop. Similarly, Verma and McKenzie (1982), Verma et al (1983b), Rawlinson and Muthyalu (1979), and Anderson (1983) reported that some seed dressing fungicides reduced stem canker in older rapeseed plants.…”
Section: Controlmentioning
confidence: 91%
“…Surveys conducted in 1977 and 1978 revealed that blackleg was present in all rapeseed growing regions of that country (Kriiger 1978(Kriiger , 1979. Similarly, little blackleg was found on winter rapeseed in England before 1977, but a substantial increase was noted in 1977 and 1978 (Gladders & Musa 1979, Humpherson-Jones 1983, Rawlinson & Muthyalu 1979 in conjunction with an increase in the intensity of rapeseed cultivation (Cook & Evans 1978). Disease incidence and yield loss were 100% and 50%, respectively, in some rapeseed fields in 1977 (Cook & Evans 1978, Gladders & Musa 1979.…”
Section: History Occurrence and Impactmentioning
confidence: 99%
“…are the most serious pathogens affecting oilseed rapes. In addition to these, damping-off and foot rot are also serious pathogens in Canada (Berkenkamp and Vaartnou 1972, Rawlinson and Muthyalu 1979, Kruger 1979, Svensson 1982. In a long-term crop rotation experiment carried out by the Department of Plant Pathology, the University of Helsinki, damping-off started to increase strongly on turnip rape after the crop had been grown on the same area twice or three times.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial yield losses occur in areas where the disease is severe. Foliar application of fungicides has been extensively evaluated in Australia (Barbetti 1974, Brown et al 1976, in England (Rawlinson & Muthyalu 1979), and in Canada (Kharbanda 1989, Xi 1987. However, marginal and variable control has resulted.…”
Section: Blackleg Of Rapeseed Caused Bymentioning
confidence: 99%